Novel 1, 8-naphthalimides substituted at 3-C position: Synthesis and evaluation of thermal, electrochemical and luminescent properties. (November 2018) - Kotowicz, Sonia; Korzec, Mateusz; Siwy, Mariola; Golba, Sylwia; Malecki, Jan Grzegorz; Janeczek, Henryk; Mackowski, Sebastian; Bednarczyk, Katarzyna; Libera, Marcin; Schab-Balcerzak, Ewa
Abstract: Novel 1, 8-naphthalimides core substituted at 3-C position via imine bond with carbazole, benzothiazole, methylindole, quinoline, benzoindole, phenylmorpholine and triphenylamine derivatives were designed, synthesized and investigated with regard to their thermal, electrochemical, and luminescence behavior. DSC measurements showed that the obtained crystalline compounds can be converted into amorphous materials with glass transition temperatures in the range of 28–54 °C, except for the molecule bearing benzoindole derivative. The prepared compounds were thermally stable with the onset of thermal decomposition in the range of 345–368 °C. Energy band gap electrochemically estimated was modulated from 2.13 to 2.52 eV. Effect of excitation wavelength on the photoluminescence relative intensity of those naphthalimides in solution was detected. Their photoluminescence maximum band was located in the range of 495–560 nm in solution with the quantum yield from 0.2 to 14.0%. In the film, they emitted light in the blue and green spectral region with quantum yields from 1.1 to 3.6%. The electroluminescence ability of core substituted 1, 8-naphthalimides was tested in the single-layer diode geometry. They were utilized as an emitting layer for both non-doped and doped single-layer OLEDs fabricated by solution processing. Additionally, calculations using density functional theory were performed to obtain the optimized ground-state geometry and distribution of the HOMO and LUMO levels of the synthesized molecules. Graphical abstract: Image 1 Highlights: The effect of the substituent attached via imine to the naphthalimide core was studied. The crystalline AzNIs could be converted into amorphous materials except for one with benzoindole. All molecules showed value of Eg below 3 eV required for organic electronics. The presence of benzothiazole and quinoline units reduced the PL quantum yields of AzNIs in solution. AzNIs with carbazole, benzoindole and triphenylamine seem to be the most promising for further investigations.